The cost of oil. (Kanopy Streaming, 2014)
The pressure to drill for oil in the Arctic has intensified with the increasing prices of crude oil. But the potential for lower oil prices is at what cost? In this feature-length documentary the Alaskan Inupiat show how oil drilling in their nearby seas will forever alter their subsistence-living lifestyle and multiply the struggles of preserving their rich cultural history. Members of the oil industry and expert scientists also highlight the predicted effects of oil drilling on the delicate Arctic ecosystem, and in turn, the effects on a society dependent on that ecosystem. Through this film viewers discover the irony of drilling for oil in order to become a more self-sustaining nation, and in doing so, likely destroying one of the last remaining self-sustaining cultures.